2018
DOI: 10.1080/1028415x.2018.1446812
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant and anti-inflammatory efficacy of caffeine in rat model of neurotoxicity

Abstract: The present findings clearly indicate that caffeine provides a significant neuroprotection against AlCl-induced neurotoxicity mediated by its antioxidant, anti-inflammatory, and anticholinesterase properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…The observed morphological lesions in the hepatic and renal tissues of AlCl 3 -intoxicated rats may explain the increased levels of the proinflammatory cytokines TNF- α and IL-1 β as compared with the CON group. The data of the present study agree with the results of Zhang et al [ 40 ], Justin-Thenmozhi et al [ 41 ], and Hosny et al [ 42 ], who found that Al exposure increased the levels of TNF- α and IL-1 β in the liver and kidney tissues of rats.…”
Section: Discussionsupporting
confidence: 93%
“…The observed morphological lesions in the hepatic and renal tissues of AlCl 3 -intoxicated rats may explain the increased levels of the proinflammatory cytokines TNF- α and IL-1 β as compared with the CON group. The data of the present study agree with the results of Zhang et al [ 40 ], Justin-Thenmozhi et al [ 41 ], and Hosny et al [ 42 ], who found that Al exposure increased the levels of TNF- α and IL-1 β in the liver and kidney tissues of rats.…”
Section: Discussionsupporting
confidence: 93%
“…Caffeine decreased activity of Na + /K + -ATPase in the cerebral cortex, hippocampus and striatum, and reduced activity of AChE in the cerebral cortex and hippocampus. Also anti-inflammatory properties of caffeine were demonstrated (decreased TNF-α level in the hippocampus and striatum) in AlCl 3 -induced neurotoxicity in rats [143].…”
Section: Non-transgenic Rodent Modelsmentioning
confidence: 89%
“…Generally, experimental studies on caffeine effects in AD demonstrated some beneficial influence on cognition. Its neuroprotective, antioxidant, anti-inflammatory and antiapoptotic activities in the neuronal tissues, led to alleviation of cognitive impairment [104,119,122,123,128,[131][132][133]136,[141][142][143]155,156,158,160,161,[164][165][166]. Many studies pointed out on favorable effects of caffeine on the hallmarks of the disease: Aβ or hyperphosphorylated tau protein [104,117,129,131,134,156,161,162,[164][165][166].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations